Penerapan Konsep Segitiga Restitusi untuk Mengembangkan Budaya Positif di Sekolah Dasar - Suryatama, Handika; Saputra, Surya Adi; Siswanto, Deny Hadi; Alghiffari, Eka Kevin (Prodi PGMI STAI Sabili Bandung, 2024)
The aim of this research is to describe phenomena in the educational environment in elementary schools related to the concept of the restitution triangle in the development of school culture. This research is a qualitative descriptive study with a focus on principled leadership as a long-term approach to developing individuals and organizations. This research involves several steps such as identifying class and school culture, applying the appropriate restitution triangle concept, establishing a positive culture based on observations, as well as implementing and evaluating the scheme. The general results of this research are the application of related strategies to instill positive discipline in students including: (1) Building positive relationships between teachers and students; (2) Explain rules and expectations clearly; (3) Increasing positive reinforcement through praise and rewards; (4) Implement appropriate and consistent consequences for violations; (5) Master social and emotional skills, such as communication, problem solving, and managing emotions.